Will people like your illustration? Popularity assessment of illustrations - Jiachen Yang; Yao Men; Yang Zhao (Electronics Letters, 2021)
Abstract Illustrations frequently appear in advertisements, films, books, etc. Research into the popularity of illustrations shows practicality and necessity already, which plays an important role in the improvement of illustrations and advertising decisions. In this letter, an Illustration Popularity Assessment Network （IPANet） is designed, inspired by the illustration creation process. Atrous convolutional layers are densely concatenated to extract image composition information and Gram matrix is used to measure the image style. We also introduce a scoring model based on ‘views’ and ‘likes’ to score the popularity of collected illustrations. The IPANet is proved to be effective according to experimental results on the scored illustrations. As far as we know, we are the first to explore the popularity of illustrations and practice successfully.